How choices of leaders are influenced by information and leaders’ impacts on contributions and wages - Nguyen, Anh Phuong (2020)
This thesis highlights the significant importance of leadership to organizational settings in which group members’ behaviours are driven by social dilemma. Using experimental methodology, we manage to investigate how the choices of leaders are influenced by the provided information about leadership candidates and how selected leaders affect group members’ contributions and wages. First of all, we find that group members offer higher salaries to leaders, who are able to demonstrate their fluent communication, need for achievement and affiliation, aversion to risk and authenticity in the written abstracts. Those leaders are also found to be less neurotic, open to experience and more self-esteem, loss-averse. Secondly, output distribution behaviour of selected group leaders is found to be positively influenced by the group members’ contributions. In addition, group members are found to be more satisfied with leaders that allocate more final outputs. Thirdly, we discover that efficient leaders’ communication is featured by high level of affiliation in general. Besides, when communicating with a group of followers, leaders’ languages are found to be friendlier, more distinctive and decisive while their languages tend to be more emotional, achievement-oriented and less self-focused, leisure-related when leaders communicate with an individual member. Fourthly, we identify key traits of efficient leaders, which are less neuroticism, Machiavellianism and more egalitarianism and ambiguity-seeking. Among those traits, leaders with high egalitarianism and low Machiavellianism are found to satisfy group members the most. Also, male leaders are found to be more ambiguity-seeking than female ones.